1996
DOI: 10.1159/000282815
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation in Autosomal Dominant Polycystic Kidney Disease without Nephrectomy

Abstract: Some transplantation centers still suggest nephrectomy in patients with autosomal dominant poycystic kidney disease (ADPKD) before kidney transplantation at least in selected cases. We wanted to learn whether prior nephrectomy is beneficial. The outcome of kidney transplantation in 47 consecutive ADPKD patients without prior nephrectomy was compared with that in matched controls with respect to complications of ADPKD. Although ADPKD patients were older than controls (mean, 50.1 vs. 40.3 years), there was no st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 18 publications
0
14
0
2
Order By: Relevance
“…However, with the development of intensive care and surgical techniques, the incidence of severe posttransplant complications was markedly decreased. Therefore, routine pretransplant native nephrectomy for ADPKD is not beneficial nowadays [11][12][13] . Some other centers suggested a 'sandwich' technique which recommended that patients were primarily scheduled for the removal of the more seriously affected native kidney before transplantation, and the remaining one thereafter [14] .…”
Section: Discussionmentioning
confidence: 99%
“…However, with the development of intensive care and surgical techniques, the incidence of severe posttransplant complications was markedly decreased. Therefore, routine pretransplant native nephrectomy for ADPKD is not beneficial nowadays [11][12][13] . Some other centers suggested a 'sandwich' technique which recommended that patients were primarily scheduled for the removal of the more seriously affected native kidney before transplantation, and the remaining one thereafter [14] .…”
Section: Discussionmentioning
confidence: 99%
“…Several authors concluded that in patients with ADPKD, nephrectomy is not indicated as a routine pretransplant procedure, having no advantages in terms of complications and survival over transplantation with both native kidneys intact [12][13][14][15]. On the contrary, some authors [16,17] suggest that the native polycystic kidneys are at risk of infectious and hemorrhagic complications after grafting, in addition to patient's discomfort and technical difficulties with graft placement.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, outcomes among 47 consecutive ADPKD patients without pretransplant nephrectomy were compared to those of 47 matched, non-ADPKD controls (880). There were no differences in 1-and 5-year graft survival rates.…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 99%
“…Only three ADPKD patients had cyst infections and two had episodes of hematuria, but in neither case was invasive intervention required. These authors concluded that routine pretransplant nephrectomy is not required for most patients with ADPKD (880). In the absence of data to the contrary, it seems reasonable to reserve pretransplant nephrectomy for ADPKD patients who have recurrent, symptomatic, cyst-related complications.…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 99%